(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
An intensification of refugee and migrant wave to the EU has initiated a more serious challenges especially in terms of its institutional and operational functionality. In addition, the crisis initiated serious dilemmas and internal divisions among Member States, both in terms of the integration approach to the refugees and migrants that have already arrived in EU as well as to the needed instruments related to closing the active transit routes and the prevention of a new mass migrations and requirements asylum. Therefore, the EU has not manifested fast, clear and effective response at the beginning of the crisis. However, the signing of the Agreement with the Turkey (March, 2016), has marked the beginning of a more serious EU approach in dealing with the crisis. The Agreement is significant because it presents a comprehensive approach in solving of the refugee and migrant crisis through the inclusion of more players, as well as through simultaneous action in reducing and eliminating the crisis causes and consequences. Still, in term of the required time for effective implementation of the Agreement, it remains open dilemma if the EU will be able for effectively solving of all crisis aspects by the end of the 2016.